Migrant youth’s emerging dietary patterns in Haiti: The role of peer social engagement - Heckert, Jessica; Boatemaa, Sandra; Altman, Claire E. (Cambridge University Press, 2015)
The present study examines whether rural-to-urban migrant youth consume a greater diversity of high-sugar beverages and fried snacks (HSBFS) compared with their peers who remain in rural areas. It also tests whether the association between migration and HSBFS diversity is moderated by migrant youth’s social engagement with their peers.Participants were recruited in August and September 2011 following the completion of primary school (6th grade) and shortly before many rural youth migrate to urban areas. Participants were re-interviewed six months later. HSBFS diversity was assessed at follow-up; analyses control for baseline and follow-up characteristics.Baseline interviews occurred in rural Southeast Haiti. Follow-up interviews of migrants occurred at urban destinations in Haiti.The sample includes 215 youth (mean age 15·9 years; 43·3 % female; 21·9 % rural-to-urban migrants) who were interviewed at baseline and follow-up.Rural-to-urban migrant youth consumed a greater diversity of HSBFS products at follow-up than their rural counterparts (b=0·70,P≤0·05). Moreover, we found that this relationship varied by level of peer social engagement. Youth who migrated and had a high degree of peer social engagement consumed 2·2 additional types of HSBFS products daily than their counterparts who remained in rural areas and had low peer social engagement.Higher HSBFS diversity among migrant youth is consistent with the patterns proposed by the nutrition transition. Interactions with peers may have an important influence as migrant youth adopt new dietary preferences. Emerging dietary patterns among youth migrants have important implications for health trajectories and the development of degenerative diseases.